2000
DOI: 10.1172/jci10902
|View full text |Cite
|
Sign up to set email alerts
|

The bile acid synthetic gene 3β-hydroxy-Δ5-C27-steroid oxidoreductase is mutated in progressive intrahepatic cholestasis

Abstract: We used expression cloning to isolate cDNAs encoding a microsomal 3β-hydroxy-∆ 5 -C 27 -steroid oxidoreductase (C 27 3β-HSD) that is expressed predominantly in the liver. The predicted product shares 34% sequence identity with the C 19 and C 21 3β-HSD enzymes, which participate in steroid hormone metabolism. When transfected into cultured cells, the cloned C 27 3β-HSD cDNA encodes an enzyme that is active against four 7α-hydroxylated sterols, indicating that a single C 27 3β-HSD enzyme can participate in all k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 32 publications
1
74
1
Order By: Relevance
“…1A). Concordant with the results of the microarray analysis, mRNA levels for 3␤-hydroxy-⌬ 5 -C 27 -steroid oxidoreductase (3␤-HSD) (33) and GABA(A) receptor-associated protein-like 1 (Gabarapl1) (34) were higher at ZT6 than ZT18 and those for Spot14, Hspa8, Hspa5, and Hsp84-1 were higher at ZT18 than ZT6. We also performed Northern analysis by using poly(A) ϩ RNA-derived sense strand cRNA (Fig.…”
Section: Resultssupporting
confidence: 73%
“…1A). Concordant with the results of the microarray analysis, mRNA levels for 3␤-hydroxy-⌬ 5 -C 27 -steroid oxidoreductase (3␤-HSD) (33) and GABA(A) receptor-associated protein-like 1 (Gabarapl1) (34) were higher at ZT6 than ZT18 and those for Spot14, Hspa8, Hspa5, and Hsp84-1 were higher at ZT18 than ZT6. We also performed Northern analysis by using poly(A) ϩ RNA-derived sense strand cRNA (Fig.…”
Section: Resultssupporting
confidence: 73%
“…CYP27A1, and 3␤-hydroxy-⌬ 5 -C 27 -steroid oxidoreductase (3␤HSD), from David Russell, University of Texas Southwestern Medical Center (13,14). Probes for other mouse genes were generated by RT-PCR using the following primers (GenBank accession numbers are provided in parentheses): constitutive androstane receptor (CAR) (AF009327) 5Ј-GGAATTCGGA-ATG and 5Ј-GCGGATGGCCTCAA; cytochrome P450 2B10 (CYP2B10) (NM 009998.1) 5Ј-GGCTTCTTGCTACTCT-TAGC and 5Ј-ATTTCCACCAGCTGTCTCAG; cytochrome P450 3A11 (CYP3A11) (NM 007818.1) 5Ј-TTTTCTGTCT-TCACAAACCGG and 5Ј-CAAACCTCATGCCAATGCAG; sterol 12␣-hydroxylase (CYP8B1) (AF090317) 5Ј-GGGTAC-CAGTCTGTAGATGG and 5Ј-AGTCTCTGGTGGAAGA-GACG; multidrug resistance-associated protein 2 (MRP2) (AF227274) 5Ј-GACTCTGACAACTTGAATGGGACC and 5Ј-CCTTCTCTCCGCTCTTGATGTTAC; organic anion transporter polypeptide (OATP2) (NM 030687) 5Ј-CATGTG-CATATGTATCCAAATCAC and 5Ј-CCTCATCACAGCT-TAGTTTTCCGT; and small heterodimer partner (SHP) (L76567) 5Ј-AAGGATCCGCTGGGAAGAAACAGGAA-CAAG and 5Ј-CTAGCTAGCTGGAGGCACCAGACTC-CATTC.…”
Section: Methodsmentioning
confidence: 99%
“…In the first reported patient, complete absence of 3␤-HSD activity was found by Buchmann et al in 1990 (2) based on the study of cultured fibroblasts. In 2000, Schwarz et al (3) reported that the same patient had a homozygous mutation representing a 2-bp deletion in exon 6 of the 3␤-HSD gene (HSD3B7) on chromosome 16p11.2-12. The human HSD3B7 gene contains six coding exons and encodes 369 amino acids; so far, 13 distinct mutations causing 3␤-HSD deficiency have been reported (4,5).…”
Section: Eficiency Of 3␤-hydroxy-⌬mentioning
confidence: 99%